Adsorption of Eosin Bluish on Roots, Stem and Leaves of Phoenix dactylifera - Manzoor, Adeela; Kanwal, Farah; Imran, Muhammad; Yunis, Ruhamah (Asian Journal of Chemistry, 2011)
Phoenix dactylifera (Date Palm) was investigated for its ability to perform as a suitable adsorbent for removal of Eosine bluish from aqueous solution. The effect of adsorbent dose, contact time, stirring speed, pH and temperature was investigated using a batch adsorption technique. The results revealed the potential of roots, stem and leaves of Phoenix dactylifera (Date Palm) fiber, as a low cost sorbent for Eosine dye examined. Acidic pH (1), low temperature (10 ºC) and low stirring speed (240 rpm) were found to be favourable conditions for the adsorption of eosin dye on all the three adsorbents. Langmuir and Freundlich isotherm equations were applied for the equilibrium data. The comparative study showed that leaves were found to be best adsorbent for removing eosin dye from aqueous solution as compared to roots and stem of Phoenix dactylifera.